Dinamika Forgiveness pada Istri Korban Perselingkuhan Suami - Kenania Roseli Dirfa; Ratriana Yuliastuti Endang Kusumiati (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Infidelity is a relationship established with someone other than one's spouse. This certainly evokes various emotions in the victim. Forgiveness is a change in an individual's behavior with the aim of reducing the motivation for revenge or distancing oneself from other individuals who have hurt them. This study aims to reveal the stages of the process and factors that influence forgiveness in a wife who is a victim of her husband's infidelity but still maintains her marriage. A qualitative research method was chosen to collect data from three participants through semi-structured interviews and observation. The results show that each participant went through four stages in the forgiveness process, namely the uncovering phase, decision to forgive, work phase, and deepening phase. Although they went through the same four stages, each participant had a different way of expressing and responding to their feelings, as well as their motivation to reconcile. This study also reveals that one of the biggest factors influencing forgiveness in the three participants was their level of religiosity.